CLASSES EVALUATION – METHODS AND TOOLS - Grabiński, Tadeusz; Barszcz – Przełożny, Barbara; Paszek, Zbigniew; Urlik, Szczepan (International Journal of Economic Practice and Policy, 2013)
This study presents a method, tools, course and results of foreign language classes evaluation conducted in the summer semester 2012/2013 in the Andrzej Frycz – Modrzewski Krakow University. Because a new evaluation procedure has been implemented at the University, the former method – based on paper forms filled in by the students – was abandoned. On the surveyanyplace.com website, a free account has been registered and the form of the evaluation questionnaire has been inserted. This coverage presents results of a taxometric analysis aimed at checking the degree of mutual correspondence (correlation) between certain criteria and instancing a graphic presentation of the evaluation results in a multidimensional perspective. In order to classify the grading criteria, the Ward’s agglomerative method, along with Euclidean metric as a measure of criteria similarity, have been used. Calculations have been made with the use of Statistica package. Results of the questionnaire show that foreign language teaching at the Andrzej Frycz Modrzewski Krakow University is conducted professionally and on a high factual level.